Macrophage Migration Inhibitory Factor: A Novel Inhibitor of Apoptosis Signal-Regulating Kinase 1–p38–Xanthine Oxidoreductase–Dependent Cigarette Smoke–Induced Apoptosis - Fallica, Jonathan; Varela, Lidenys; Johnston, Laura; Kim, Bo; Serebreni, Leonid; Wang, Lan; Damarla, Mahendra; Kolb, Todd M.; Hassoun, Paul M.; Damico, Rachel (American journal of respiratory cell and molecular biology, 2016)
Cigarette smoke (CS) exposure is the leading cause of emphysema. CS mediates pathologic emphysematous remodeling of the lung via apoptosis of lung parenchymal cells resulting in enlargement of the airspaces, loss of the capillary bed, and diminished surface area for gas exchange. Macrophage migration inhibitory factor (MIF), a pleiotropic cytokine, is reduced both in a preclinical model of CS-induced emphysema and in patients with chronic obstructive pulmonary disease, particularly those with the most severe disease and emphysematous phenotype. MIF functions to antagonize CS-induced DNA damage, p53-dependent apoptosis of pulmonary endothelial cells (EndoCs) and resultant emphysematous tissue remodeling. Using primary alveolar EndoCs and a mouse model of CS-induced lung damage, we investigated the capacity and molecular mechanism(s) by which MIF modifies oxidant injury. Here, we demonstrate that both the activity of xanthine oxidoreductase (XOR), a superoxide-generating enzyme obligatory for CS-induced DNA damage and EndoC apoptosis, and superoxide concentrations are increased after CS exposure in the absence of MIF. Both XOR hyperactivation and apoptosis in the absence of MIF occurred via a p38 mitogen-activated protein kinase-dependent mechanism. Furthermore, a mitogen-activated protein kinase kinase kinase family member, apoptosis signal-regulating kinase 1 (ASK1), was necessary for CS-induced p38 activation and EndoC apoptosis. MIF was sufficient to directly suppress ASK1 enzymatic activity. Taken together, MIF suppresses CS-mediated cytotoxicity in the lung, in part by antagonizing ASK1-p38-XOR-dependent apoptosis.